UZBEK AND INDIAN WEDDING CUSTOMS - Jumayev, M.A; Kenjayeva, Ozoda (Educational Research in Universal Sciences, 2023)
This article reveals the role and importance of the cultural sides of two nations wedding party.Each nation has its own customs which shows their history, nationality and some essential events. In wedding days every nation try to do their own historical traditional customs.